Additive Manufacturing: Unlocking the Evolution of Energy Materials. Issue 10 (25th July 2017) - Zhakeyev, Adilet; Wang, Panfeng; Zhang, Li; Shu, Wenmiao; Wang, Huizhi; Xuan, Jin
Abstract: The global energy infrastructure is undergoing a drastic transformation towards renewable energy, posing huge challenges on the energy materials research, development and manufacturing. Additive manufacturing has shown its promise to change the way how future energy system can be designed and delivered. It offers capability in manufacturing complex 3D structures, with near‐complete design freedom and high sustainability due to minimal use of materials and toxic chemicals. Recent literatures have reported that additive manufacturing could unlock the evolution of energy materials and chemistries with unprecedented performance in the way that could never be achieved by conventional manufacturing techniques. This comprehensive review will fill the gap in communicating on recent breakthroughs in additive manufacturing for energy material and device applications. It will underpin the discoveries on what 3D functional energy structures can be created without design constraints, which bespoke energy materials could be additively manufactured with customised solutions, and how the additively manufactured devices could be integrated into energy systems. This review will also highlight emerging and important applications in energy additive manufacturing, including fuel cells, batteries, hydrogen, solar cell as well as carbon capture and storage. Abstract : An overview of novel additively manufactured energy materials and their applications in renewable energy generation, storage and conversion is given in this comprehensive Review. It also provides the perspective on how additive manufacturing technology could unlock the evolution of energy materials in the future.